Conservation Subdivision: Design Phase – Wetland Considerations - Mark Hostetler (EDIS, 2010)
WEC281, a 4-page illustrated fact sheet by Mark Hostetler, discusses issues surrounding on-site protection of wetlands and strategies to create wetlands that conserve biodiversity when land is subdivided. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, March 2010.